1997
DOI: 10.1128/iai.65.10.4236-4242.1997
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B27 modulates the survival of Salmonella enteritidis in transfected L cells, possibly by impaired nitric oxide production

Abstract: Reactive arthritis is triggered by certain microbes that cause primary infections mainly on the gastrointestinal or urogenital mucosa. The disease is strongly associated with HLA-B27. Long persistence of causative microbes or their structures in the body has been thought to have an important role in the pathogenesis of reactive arthritis. This suggests that the elimination of the microbes causing reactive arthritis is ineffective or disturbed in HLA-B27-positive individuals developing this complication. We exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This has prompted us to study whether B27 expression alters the function of host cells that encounter ReA‐triggering bacteria in vitro. We observed impaired elimination of Salmonella enteritidis in B27‐transfected cell lines as compared with appropriate controls (16, 17). Further studies showed that B27‐expressing cells were more permissive of intracellular replication of S enteritidis .…”
mentioning
confidence: 71%
“…This has prompted us to study whether B27 expression alters the function of host cells that encounter ReA‐triggering bacteria in vitro. We observed impaired elimination of Salmonella enteritidis in B27‐transfected cell lines as compared with appropriate controls (16, 17). Further studies showed that B27‐expressing cells were more permissive of intracellular replication of S enteritidis .…”
mentioning
confidence: 71%
“…It has long been known that patients with reactive arthritis triggered by Yersinio or Salmonella show prolonged immune responses to these microorganisms, suggesting bacterial persistence (reviewed in (6.S)). Recently, B27, unlike other HI.A I genes, has been shown to be associated with marked impairment of clearance of intracellular bacteria from transfected human and mouse cell lines (66,67), with impaired nitric oxide production suggested as at least one possible mechanism. Increased bacterial persistence would then be expected to provoke a heightened immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the main function of the major histocompatibility complex (MHC) class I molecules has been thought to be antigen presentation (16), but an increasing number of reports indicate other putative functions. We have previously demonstrated impaired elimination of Salmonella enteritidis in HLA–B27–transfected human monocytic cells compared with HLA–A2–transfected counterparts (17), and in HLA–B27–transfected murine fibroblasts compared with HLA–B7 or human β 2 ‐microglobulin–transfected counterparts (17, 18). Certain mouse MHC class I molecules have been shown to play a role in modulating the replication of intracellular Sindbis virus (19).…”
mentioning
confidence: 99%